Acute phlegmonous gastritis: A case report - Haley Durdella; Scott Everett; Jerri A. Rose (Journal of the American College of Emergency Physicians Open)
Abstract Acute phlegmonous gastritis (APG) is an extremely uncommon and potentially rapid fatal systemic infection with very few reported cases in the literature. This case report demonstrates a case of idiopathic APG in an afebrile, otherwise healthy individual that resolved with broad‐spectrum antibiotic therapy and did not require operative management.